The frequency of repeat general anaesthesia for teeth extractions in children - S. S. ALBADRI, F. D. JARAD, G. T. LEE, & I. C. MACKIE (IAPD and Blackwell, 2006)
In 1990, the Poswillo Report concluded that ‘the use of general anaesthesia should be avoided when possible’ [1], and the UK General Dental Council guidelines state, ‘General anaesthesia is a procedure which is never without a risk’ [2].